Last mile delivery with lockers, formulations and heuristics - Oliveira, Willian Jorge Pereira (2022)
The demand for delivering goods to individuals has increased due to several factors such as urbanization, the growth of e-commerce, and the popularization of the internet. There are several challenges to deal and in the face of this, there is a constant search for new alternatives. In this scenario, among other solutions, lockers emerged, which are cabinets equipped with a self-collection interface, strategically positioned to serve customers asynchronously. In this work, we approach different formulations of the last mile delivery problem with lockers, considering the size of parcels and compartments and the probabilistic characteristic of the problem due to uncertainty about users accepting to use the locker. In all formulations, the objective is to decide the location of lockers and vehicle routes in order to minimize the cost of last-mile delivery. For this, we propose heuristics and mathematical models to deal with different problems, we create instances based on real data, and we perform several computational tests. We evaluated different scenarios and estimate how much the use of lockers can generate savings. In the probabilistic problem, we were able to simulate different scenarios, where all users accept or reject the use of lockers. Doing this, we were able to measure the savings that the use of lockers can generate and, thus, make decisions about the investment to be made in the construction and promotion of the use of lockers. Keywords: Combinatorial optimization. Vehicle routing. Facility location. Location Routing Problem. Last mile delivery. Parcel Lockers.